Norm(al)ization of Lexical Re-standardization. (Case Study: Croatian Educational System) - Peti-Stantić, Anita; Langston, Keith (2010)
This paper will investigate the norm(al)izationn processes of lexical re-standardization which have been taking place within the educational system of the Republic of Croatia since its proclamation of independence in 1991. Following Bourdieu (1991), who argues that language plays the central role in the social reproduction carried out through education, and Joseph (2006), who states that education is always at the center of all debates over language and politics, the authors start from the position that the educational system is a primary arena for the creation, performance, and reproduction of language in its role as a symbol of national identity. The main goal of this research is to identify the explicit procedures and practices, as well as implicit goals, of representatives of institutions that are in charge of the implementation of educational language policies. The authors will use methods of qualitative analysis, including critical approaches, in which language restandardization is understood not as an incidental and natural outcome of a political situation, but rather as a manifestation of asymmetrical power relations based on social structures and ideologies that position groups and their languages hierarchically within a society (Ricento, 2006). For that reason this research focuses on discouses in which social relations are reflected, reproduced, and contested, rather than on the language as a whole. The analysis compares materials from both before and after 1991 and includes the following types of texts: 1. Instructional plans (from 1972, 1988/89 and 1999) and textbooks for four school subjects: Croatian language and literature, history, geography, and biology 2. Other major documents issued by responsible institutions 3. Lectures and texts presented at continuing education meetings for teachers. These findings will be compared with those from a combined quantitative and qualitative analysis conducted earlier on the basis of questionnaires and interviews on language issues that were administered to teachers and students. The results of this research will be a critical examination of language policy and planning in the context of the Croatian educational system, the discursive practices through which these policies are legitimized, and their consequences for different social groups (primarily teachers and students).
Projekt MZOS
ENG